1991
DOI: 10.1111/j.1348-0421.1991.tb01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Cytomegalovirus Infections by Direct Immunoperoxidase Staining with Human Monoclonal Antibody against an Immediate‐Early Antigen

Abstract: Direct immunoperoxidase technique using a horseradish peroxidase (HRP)-conjugated Fab' fragment of human monoclonal antibody (humab C7), designated HRP-C7, was evaluated as a rapid diagnosis of cytomegalovirus (CMV) infection. A total of 138 clinical specimens consisting of 124 urine samples and 14 oral swabs were examined for CMV by the direct HRP-C7 staining in comparison with conventional virus isolation. The number of CMV-positive samples by each method was 40 (29.0%) for the former and 37 (26.8%) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Several methods are used to diagnose CMV infection, including histologic examination, CMV antigenemia, and PCR assay. [7][8][9] Among them, CMV antigenemia and PCR assay using whole blood potentially reflect the reactivation of CMV in the whole body, but does not necessarily indicate CMV infection in the colonic mucosa. Indeed, there are several reports of reactivation of CMV in the plasma of patients with collagen disease and AIDS without gastrointestinal involvement of CMV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods are used to diagnose CMV infection, including histologic examination, CMV antigenemia, and PCR assay. [7][8][9] Among them, CMV antigenemia and PCR assay using whole blood potentially reflect the reactivation of CMV in the whole body, but does not necessarily indicate CMV infection in the colonic mucosa. Indeed, there are several reports of reactivation of CMV in the plasma of patients with collagen disease and AIDS without gastrointestinal involvement of CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] For diagnosis of CMV infection in the gastrointestinal tract, combined CMV antigenemia assay and detection of CMV inclusion bodies in biopsy specimens from the gastrointestinal mucosa by either hematoxylin and eosin (H&E) staining or immunohistochemistry (IHC) using anti-CMV monoclonal antibodies has been proposed. 1 It is often difficult, however, to accurately diagnose CMV infection in patients with UC, 10 even when using this combined diagnostic method.…”
mentioning
confidence: 99%
“…A chest roentgenogram showed that there were marked bilateral interstitial in®ltrates on February 26. Because CMV antigenemia was identi®ed (by HRP-C7 method [Eizuru et al, 1991]) in addition to the clinical features, ganciclovir treatment was started from March 3. No other pathogen was isolated from his sputum specimens by bacterial and fungal cultures.…”
Section: Patient and Methodsmentioning
confidence: 99%
“…The diagnosis of UC was made by clinical, endoscopic, and histological findings based on standard criteria (16,17).…”
Section: Patientsmentioning
confidence: 99%